PG78 A multi-professional education programme: simulation enhances staff preparedness for dealing with Covid 19 pandemic. (10th November 2020) - Quayle, Alexandra; Harrison, Nick; McGuffie, Rochelle
Abstract : Introduction: The novel coronavirus – Covid 19 pandemic has presented huge challenges to healthcare provision worldwide. The virus is an unknown quantity. The multisystem pathology and highly contagious nature, has caused healthcare capacity to become overwhelmed during the peak. Learning from other countries' experience, at Northern Lincolnshire and Goole hospital Trust we created a multi-pronged approach to rapidly educate staff and test the clinical set up for managing a surge of patients with Covid 19. 1 Methods: In-situ simulations were conducted in the Emergency departments, Respiratory wards and ICU, evaluating the trust logistics and clinical management of the acutely deteriorating patient. A Covid 19 education package was developed comprising lectures covering pathophysiology, assessment, decision making tools, management protocols and operating procedures. Theory was consolidated with rotating small group simulations in vacant operating theatres. Familiarisation with Personal Protective Equipment (PPE), Public Health England guidance and practising donning and doffing started the session. Utilising both full body manikins, and part task trainers we simulated the following suspected/Covid 19 clinical scenarios; Emergency intubation, ventilation and transfer Conducting anaesthesia and surgery Caesarean section, and insertion of labour Epidural Cardiac arrest Proning and unproning the ventilated patient in ICU Results: Sessions were run eight per day, over two weeks, populated with eight multi-professional staff (approximately fifty/day). Attendees included doctors from critical care, surgery, Emergency and respiratory medicine, all theatre and recovery nursing and operating department practitioners. In -situ scenarios elucidated logistical challenges relating to space, PPE, drugs, equipment and technical aspects when performing emergency intubation in situ. Discussion: With the Covid 19 pandemic rapidly escalating, a coordinated approach of assessing our trust's logistics and clinical protocols was needed, as well as effective education, cross speciality and health care professions, together with cross skilling in practical procedures. Speed of delivery was imperative and this programme was created and rolled out within two weeks. In North Lincolnshire Covid 19 infection rates remained slower that many UK areas, permitting a timely window of training. Challenges faced were the availability of training locations, spacious enough to permit social distancing, the differing needs of healthcare professionals, and the frequent changes to national guidance. Simulation both in -situ and class room based together with clinical skills drills was invaluable in facilitating the learning. Verbal reports from participants demonstrated decreased anxiety, and improved confidence when faced with suspected/COVID patients, and familiarisation with the PPE guidance. 2 References: https://www.who.int/emergencies/diseases/novel-coronavirus-2019/training/simulation-exercise. Simulation-based training programme and preparedness testing for COVID-19 using system integration methodology HMS. Lababidi et al BMJ Simulation and Technology Enhanced learning 27 May 2020 online